SEMINAR UNTUK MENINGKATKAN KOMPETENSI GURU DALAM PEMBELAJARAN MELALUI STEAM DI PAUD DESA PASIR TANJUNG JONGGOL KECAMATAN TANJUNG SARI, KABUPATEN BOGOR, JAWA BARAT - Sri Juwita Kusumawardhani; Fellianti Muzdalifah; Yufiarti; Erik (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2022)
Abstract STEAM is an approach that integrates Science, Technology, Engineering, Mathematical, and Arts in line with the skills needs of the 21st century. STEAM has become a content in the 2013 curriculum that has been used in Indonesia, but according to the results of interviews with PAUD Principals in the Desa Pasirtanjung, the teachers in this village have not received any training related to the STEAM learning model. This seminar will be held on Wednesday, July 20, 2022, pk. 09.00 – 11.00. The results of this activity found that classes filled with students aged 3 to 3.5 years were only given demonstrations about STEAM and parents needed to be given education so they could provide support in the learning process with STEAM. The conclusion of this activity was that early childhood teachers in Desa Pasirtanjung became more aware that STEAM learning was very easy to implement using teaching materials that could be found in their everyday environment and became enthusiastic in applying them in the classroom. Suggestions related to this activity is the execution for intensive training thus they will be doing more practicum in order to improve the skills of the teachers. Also, there is a follow-up and evaluation needed regarding the application of the STEAM learning model in Paud Desa Pasirtanjung so that they can see the significance and development of the skills of the teachers in implementing this learning. In order to have similar perception about STEAM learning we suggest to educate parents about it thus they can give fully support to teachers at school and their kids at home. Abstrak STEAM adalah pendekatan yang mengintegrasikan ilmu Science, Technology, Engeenering, Mathematic, dan Arts yang sejalan dengan kebutuhan keterampilan abad 21. STEAM ini sudah menjadi muatan di dalam kurikulum 2013 yang sudah digunakan di Indonesia, namun sesuai dengan hasil wawancara dengan Kepala Sekolah PAUD di Desa Pasirtanjung, para guru di desa ini belum mendapat pelatihan terkait model pembelajaran STEAM. Kegiatan seminar ini dilaksanakan pada hari Rabu, 20 Juli 2022, pk. 09.00 – 11.00. Hasil dari kegiatan ini ditemukan bahwa kelas yang diisi oleh siswa berusia 3 hingga 3.5 tahun hanya diberikan demonstrasi mengenai STEAM serta orangtua perlu diberikan edukasi agar dapat memberikan dukungan dalam proses pembelajaran dengan STEAM, Kesimpulan dari kegiatan ini para guru Paud di Desa Pasirtanjung menjadi lebih sadar bahwa pembelajaran STEAM sangat mudah diimplementasikan menggunakan bahan ajar yang dapat ditemukan di lingkungan sehari-hari dan menjadi antusias dalam menerapkannya di kelas. Saran terkait kegiatan ini adalah perlu adanya pelatihan yang lebih intensif dengan lebih banyak melakukan praktikum sehingga keterampilan para guru menjadi lebih terasah. Ada follow-up terkait penerapan model pembelajaran STEAM di Paud Desa Pasirtanjung sehingga bisa melihat perkembangan dari keterampilan para guru dalam menerapkan pembelajaran ini. Perlu memberikan orangtua edukasi mengenai pentingnya model pembelajaran STEAM ini sehingga mereka dapat memberikan dukungan baik kepada guru di sekolah maupun anak-anaknya di rumah.